The Effect of Tax Planning and Deferred Tax Expense on Earnings Management on Manufacturing Companies Listed In The Indonesia Stock Exchange - Noviana Mulyani, Kartika Hendra Titisari & Riana Rachmawati Dewi (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This study aims to examine the effect of tax planning and deferred tax expense onearnings management practices. Population in the study were all manufacturingcompanies listed on the Indonesia Stock Exchange. Sampling method used ispurposive sampling method by using the criterion of research sample data, so thatobtained sample of 84 annually report of manufacturing company during period ofyear 2014 – 2016. Data analysis method using descriptive statistical test, classicalassumption test and multiple linear regression. The results of the study provideempirical evidence that earnings management is not influenced by tax planning andearnings management are affected negatively and significantly by deferred taxexpense. Meanwhile, simultaneously proves that tax planning and deferred taxexpense have significant effect to earnings management variable. Based on thecoefficient of determination proves that 11,5% variable earnings management canbe explained by variable tax planning and deferred tax expense. While 88,5% othervariables which are not used in this research influence earnings managementvariable.Keywords: TaxjPlanning, DeferrediTaxlExpense, EarningsuManagement